Assessment of Production and Utilization Practices of Orange-Fleshed Sweet Potatoes (Ipomoea Batatas L.) in Sidama Region, Ethiopia. (30th September 2022) - Hendebo, Miheret; Ibrahim, Ali Mohammed; Gurmu, Fekadu; Beshir, Hussien Mohammed
Abstract : Sweet potato ( Ipomoea batatas L.) is an important crop which ensures food security in developing countries. It can be harvested at any stage as needed, thereby providing a flexible source of food and income for rural families that are most vulnerable to crop failures and cash income fluctuations. The production and consumption of orange-fleshed sweet potatoes (OFSP) by smallholder farmers in the Sidama region of Southern Ethiopia were explored in this study to identify key problems and opportunities in OFSP production. A preliminary investigation and rudimentary data collection were used to gather data. The data were analyzed using descriptive statistics, multiple linear regression, and index grading. Based on the descriptive analysis, smallholder farmers have small landholdings of 0.51 ha per family. Farmers conserve their planting materials by leaving them in the field. This causes the materials to be extensively infested with diseases, insects, and other vertebrate pests. Farmers (54.4%) do not apply inorganic fertilizersassuming that it stimulates more vegetative growth and results in tasteless storage roots. The continuous cultivation of OFSP without fertilizer application results in nutrient depletion and reduced yield. Further, the production and utilization of OFSP in the Sidama region is constrained by factors such as diseases, lack of storage facilities, lack of planting materials, drought, insect pests, low market price, and shortage of money to purchase inputs. According to the index ranking, drought, shortage of planting material, diseases, and insect pests were the most important. Combinations of social, ecological, and economic factors limit the production of sweet potatoes and therefore, a stronger extension system on agronomic practices and credit system should be made accessible to the farmers.